447 Pathology of conduction tissue in cardiac amyloid: correlation with arrhythmic manifestations. (17th December 2020) - Alfarano, Maria; Chimenti, Cristina; Verardo, Romina; Galea, Nicola; Francone, Marco; Miraldi, Fabio; Frustaci, Andrea
Abstract: Aims: Pathology of conduction tissue (CT) and relative arrhythmic manifestations in living subjects with cardiac amyloid (CA) have never been reported. Methods and results: In 17 out of 45 consecutive patients with CA, a left ventricular (LV) endomyocardial biopsy included CT sections. Extensive clinical examination, non-invasive (resting ECG, Holter monitoring, echocardiography), and invasive cardiac studies (selective coronary angiography, LV angiography, and LV endomyocardial biopsy) were performed in all patients. Cardiac magnetic resonance (CMR) was performed in 12 of the 17 patients (70%). CT was identified by Aschoff-Monckeberg histologic criteria associated to positive immunostaining for HCN4. Degree of CT infiltration was defined as mild when ≤ 30% of CT area was replaced by fibrous tissue and Congo red+ material, moderate in 30–70% CT area involvement and severe in > 70% CT cell area replacement. CT infiltration was correlated with ventricular arrhythmias, echocardiographic LV maximal wall thickness (MWT) and type of amyloid protein identified by myocardial immunohistochemistry. CMR confirmed the presence of cardiac hypertrophy with preserved systolic function in all but one patient. LGE was present in all patients, predominantly with diffuse (5/11) or subendocardial (4/11) pattern compared to focal (2/11). In 7/11 patients T1 mapping sequences have been acquired; nT1 and ECV were increase in all patients (nT1: 1171 ± 61 ms; ECV: 59.9 ± 7.5%). Mild CT involvement was observed in 5 cases; moderate in 3; severe compromise in 9. CT involvement was associated with a parallel infiltration of CT artery. CT infiltration correlated with severity of arrhythmias (Spearman rho = 0.8, P < 0.001) but not with age, MWT or type of amyloid protein. In particular, major ventricular tachyarrhythmias requiring pharmacologic treatment or ICD implantation occurred in 7 patients with severe, 1 patient with moderate and none with mild CT infiltration. Pacemaker implantation was required in 3 patients with complete CT area replacement. Conclusion: CA associated arrhythmias correlate with severity of CT infiltration. CT involvement is independent from type and severity of CA suggesting a variable affinity of amyloid protein to CT.